1)
x-y=6
x=6+y 6+у+6у+у^2=-4
у^2+7у+10=0
у1= -2
у2= 5
х1= 6+2= 8
х2= 6-5 = 1
ответ: (8; -2) ; (1;5)
5)
у-х+3=0
-х=-3-у
х= 3-у 3-у-1=y^2
-у^2-у+2=0
y^2+y-2=0
y1= 1
y2= -2
x1= 3-1 = 2
x2= 3+2 = 5
ответ: (2;1) ; (5;-2)
3)
x-y=1
-y=1-x
y= x-1 x^2-2x+2-26=0
x^2-2x-24=0
x1= 6
x2= -4
y1= 6-1 = 5
y2= -4-1 = -1
ответ: (6;5) ; (-4; -1)
Пошаговое объяснение:
(x - 20 )*3= x + 20
3x - 60 = x + 20
3x - x = 20+60
2x = 80
x = 80 : 2
x = 40л было в каждом бидоне первоначально
2*(14-x) = 1,5(14+x)
28 - 2x = 21 + 1,5x
1,5x + 2x = 28 - 21
3,5x = 7
x = 7 : 3,5
x = 2км/ч скорость течения
2*(14-2) = 2*12=24км расстояние между пристанями